Laser lithotripsy of difficult bile duct stones: results in 60 patients using a rhodamine 6G dye laser with optical stone tissue detection system. Issue 6 (1st December 1998) - Hochberger, J; Bayer, J; May, A; Mühldorfer, S; Maiss, J; Hahn, E G; Ell, C
Abstract : Introduction —Laser lithotripsy of bile duct stones has become a widely accepted endoscopic treatment modality for giant, impacted, or very hard stones. The procedure is usually carried out under direct endoscopic control in view of the potential risk of bile duct injuries in "blind" laser application. Aims —To investigate the use of a rhodamine 6G laser lithotriptor with an integrated optical stone tissue detection system (oSTDS). Methods —From 1 September 1991 to 7 March 1997, 60 patients with giant or impacted common bile duct stones refractory to endoscopic papillotomy stone extraction, and mechanical lithotripsy were treated via the endoscopic retrograde route using a rhodamine 6G dye laser (595 nm, 2.5 μs, 80–150 mJ pp, Lithognost Telemit/Baasel Corp., Germany) with integrated oSTDS. In case of tissue contact oSTDS cuts off the laser pulse after 190 ns (transmission of 5–8% of the total pulse energy). 47 patients (78.3%) were subjected to x ray targeting (oSTDS) alone, five (8.3%) to choledochoscope targeting alone, and eight (13.3%) to both techniques. Results —At the end of treatment 52 (87%) patients were completely stone-free. The only major complications included transient haemobilia, cholangitis, and pancreatitis in five patients. All five were successfully treated by conservative methods. Conclusions —Laser lithotripsy using the described rhodamine 6G dye laser with oSTDS seems to be safe and effective and allows "blind" fragmentation of difficult common bile duct stones under radiological control only.